Ultra-fast polariton dynamics in an organic microcavity - Polli D.; Brida D.; Rajendran S.K.; Michetti P.; Clark C.; Adawi A.M.; Coles D.; Virgili T.; Cerullo G.; Lidzey D.G. (EPJ Web of Conferences, 2013)
We study an organic semiconductor microcavity operating in the strong-coupling regime using femtosecond pump-probe spectroscopy. By probing the photo-induced absorption bands, we characterize the time-dependent population densities of states in the two polariton branches. We found evidence of a scattering process from the upper-branch cavity polaritons to the exciton reservoir having a rate of (150 fs)-1. A slower process similarly populates lower-branch polaritons with a rate of around (3ps)-1